First reported case of systemic envenoming by the Sri Lankan keelback (Balanophis ceylonensis). (January 2015) - Fernando, W.K.B.K.M.; Kularatne, S.A.M.; Wathudura, S.P.K.; de Silva, A.; Mori, A.; Mahaulpatha, D.
Abstract: Envenoming by colubrid snakes is rarely reported. However, some colubrid snakes (e.g. Rhabdophis tigrinus and Rhabdophis subminiatus ) have caused severe systemic envenoming. We report here the first case of a bite with systemic envenoming by Balanophis ceylonensis, an opisthoglyphous natricine colubrid, in Sri Lanka. A 33-year-old healthy male field biologist was bitten while handling the snake for photography. Within 5 min of the bite on the dorsum of the right hand, he reported severe occipital headache, photophobia, chills and transient loss of consciousness. He vomited blood-stained gastric contents and bled from venepuncture sites. He had a markedly elevated INR and positive D-dimer test suggestive of significant coagulopathy that was treated with infusions of fresh frozen plasma. He recovered and left hospital after 96 h and subsequent investigations, including electroencephalogram, were normal. We conclude that B. ceylonensis should be regarded as a medically significant venomous snake. This case highlights the need for further studies of the oral secretions (venoms) of colubrid snakes. Highlights: Envenoming by colubrid snakes is rarely reported, but is attracting increased attention. Balanophis ceylonensis, an opisthoglyphous natricine colubrid, endemic in Sri Lanka. A 33-year-old healthy young male field biologist was bitten by B. ceylonensis on the hand. He developed, severe headache, photophobia and severe coagulopathy. This suggests B. ceylonensis is a medically significant venomous colubrid and needs venom studies.